Evaluation on reheater tube failure - Purbolaksono J.; Hong Y.W.; Nor S.S.M.; Othman H.; Ahmad B. (2023)
This paper presents investigation study on the failed reheater tube by finite element modeling, dimensional measurements and microscopic examinations. The failed tube was situated in horizontal position and facing directly to the incoming hot flue gas from furnace region. Scale thickness of as-received tube samples of the failed tube and its neighbor tubes is measured in order to estimate the average scale growth rates. The estimated scale growth rate is used to generate geometries of the scale for finite element models. Operational and allowable stresses of the tube at the corresponding average tube temperatures and service hours are presented. Results obtained from finite element analysis are shown to be in good conformity with the findings from the microscopic examination. 2008 Elsevier Ltd. All rights reserved.